2012
DOI: 10.1111/j.1474-9726.2012.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Human serum metabolic profiles are age dependent

Abstract: Summary Understanding the complexity of aging is of utmost importance. This can now be addressed by the novel and powerful approach of metabolomics. However, to date, only a few metabolic studies based on large samples are available. Here, we provide novel and specific information on age‐related metabolite concentration changes in human homeostasis. We report results from two population‐based studies: the KORA F4 study from Germany as a discovery cohort, with 1038 female and 1124 male participants (32–81 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
270
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 298 publications
(299 citation statements)
references
References 47 publications
22
270
4
3
Order By: Relevance
“…The levels of metabolites depend on multiple modifiable factors, such as lifestyle and environment (9)(10)(11)(13)(14)(15)(16). We therefore considered a number of confounding effects, e.g., physiological parameters (age, sex, BMI, and systolic BP), lifestyle (physical activity, alcohol intake, and smoking), glucose levels (HbA 1c and fasting glucose), lipid levels (HDL-C and triglycerides), and medication usage (statins, b-blockers, ACE inhibitors, and ARBs).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The levels of metabolites depend on multiple modifiable factors, such as lifestyle and environment (9)(10)(11)(13)(14)(15)(16). We therefore considered a number of confounding effects, e.g., physiological parameters (age, sex, BMI, and systolic BP), lifestyle (physical activity, alcohol intake, and smoking), glucose levels (HbA 1c and fasting glucose), lipid levels (HDL-C and triglycerides), and medication usage (statins, b-blockers, ACE inhibitors, and ARBs).…”
Section: Discussionmentioning
confidence: 99%
“…The assay procedures were previously described in detail (27). For KORA S4 and F4, identical qualitycontrol procedures (9,13), which are explained in details in our previous publications, were used. In KORA F4, 131 metabolites of the initially targeted 163 metabolites passed all quality-control criteria: hexose (H1), 24 acylcarnitines, 14 amino acids, 13 sphingomyelines, 34 phosphatidylcholines (PCs), diacyl (aa), 37 PCs acyl-alkyl (ae), and 8 lysoPCs.…”
Section: Metabolomics Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the homeostasis of ceramide metabolism may be critical in regulating lifespan and age‐associated diseases (Cutler & Mattson, 2001; Rao et al ., 2007). Indeed, it has been increasingly recognized, from the cellular to human level, that perturbations in ceramide metabolism are associated with longevity (Yu et al ., 2012; Gonzalez‐Covarrubias et al ., 2013; Cutler et al ., 2014; Huang et al ., 2014) and the development and progression of many age‐related diseases including cancer (Alberg et al ., 2013), atherosclerosis (Ichi et al ., 2006), insulin resistance and diabetes (Holland et al ., 2007; Holland & Summers, 2008; Boon et al ., 2013), Alzheimer's disease (Mielke et al ., 2012), and Parkinson's disease (Mielke et al ., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Yu et al . (2012) analysed 131 targeted metabolites in 2162 individuals from the KORA study, while we analysed 280 untargeted metabolites in 6055 twins from the TwinsUK cohort (Menni et al ., 2013b). Both studies identified half of the analysed metabolites to be associated with chronological age.…”
Section: Omics and Agingmentioning
confidence: 99%